Experiences and Challenges of International Faculty in US Higher Education: Perspectives from Two Mid-Career Chinese Female Faculty (Comparative & International Education Series, 2021)
A growing body of literature explores challenges international faculty encounter in their professional life. However, little attention is given to the professional experiences of international faculty who are mid-career and may have already obtained tenure. In this study, we share our experiences and challenges as mid-career Chinese female faculty in literacy and language education. The transnational feminist framework enables us to critically examine how multiple social constructs play a role in creating sites of conflicts and negotiating power relations.  We also present both theoretical and practical implications to the field and call for institutional support and culturally sensitive mentorship.